Improving Student Learning Outcomes in Civics Lessons in Class VII-5 Using the Lecture Method Olus Demonstration and Exercises at UPT SPF SMP Negeri 2 Sunggal Academic Year 2022/2023 - Baktiana (Indonesian Journal of Educational Science and Technology, 2023)
The aim of this research is to find out how to improve learning outcomes at Sunggal 2 State Middle School. especially class VII-5 so that through the use of lecture methods plus demonstrations and exercises, learning outcomes in Civics lessons can be influenced. This research uses a quantitative approach using the demonstration method. The subjects in this research were students in class VII-5 at UPT SPF SMP Negeri 2 Sunggal for the 2022/2023 academic year, totaling 32 students consisting of 16 male and 16 female students. The data collection technique was carried out using the technique of percentage of individual absorption capacity and classical completeness, namely: individually at least 25% and classically 100%. And by conducting observations with teachers regarding the implementation of learning through the use of lecture methods plus demonstrations and exercises as well as observing students. The results of this research are (1) Improving the learning outcomes of PPKn students in class VII-5 UPT SPF SMP Negeri 2 Sunggal for the 2022/2023 academic year. This can be seen from the results of observations during demonstrations by these students obtained from cycle I and cycle II. namely: 20% and 73% (2) Applying the discussion method in class VII-5 for the 202/2023 academic year can improve learning outcomes in material learning to increase awareness of the 1945 Constitution of the Republic of Indonesia.